أثر خصائص المنظمة المتعلمة على التميز المؤسسي في القيادة العامة لشرطة الفجيرة :الابتكار المؤسسي متغري وسيط - محمد علي داد محمد
This study discussed the impact of the characteristics of the educated organization on the institutional excellence of the Fujairah Police. The problem is that despite the existence of a relationship between the effectiveness of the learning organization and the achievement of excellence and innovation, the interest of the General Command of the Fujairah Police in the characteristics of the learning organization has appeared through training only, while there are shortcomings in the processes (empowerment, motivation and work teams) that resulted in the reluctance of employees to participate in Corporate Excellence Awards. Therefore, the study aimed at diagnosing the availability of the characteristics of the learning organization, and analyzing the impact of the characteristics of the learning organization in achieving institutional excellence and institutional innovation for the Fujairah Police. It also aimed to demonstrate the role of institutional innovation as an intermediary variable between the learning organization and institutional excellence. The researcher adopted the quantitative analytical descriptive approach, and a random sample of ( ) employees was chosen. The skew coefficient, the formative validity test, the factorial analysis, and the confirmatory factor analysis. Among the most important results of the study: The level of possessing the characteristics of the educated organization in the Fujairah Police General Command was medium. There is a significant effect of the characteristics of the educated organization in achieving institutional excellence in the Fujairah Police General Command. Training, development and motivation are two important factors for improving performance and achieving a competitive advantage. There is a relationship between the learning organization and training, and between improving performance and achieving a competitive advantage. There is a significant impact of institutional innovation on institutional excellence in the Fujairah Police General Command. The study recommended the Fujairah Police General Command to enhance the process of participation in decision-making as a means of continuous development and improvement. As well as enhancing the leadership support provided by motivating employees and urging them to introduce and apply the contents of the learning organization because of its importance.